KARAKTERISTIK PEKARANGAN ETNIS JAWA UNTUK MENDUKUNG KETAHANAN PANGAN MASYARAKAT DI DAS KARANG MUMUS KALIMANTAN TIMUR - Penny Pujowati (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2016)
The pekarangan is one form of agricultural open space. Empowerment pekarangan that has a shape and land cover pattern that resembles a complex agroforestry systems and the diversity of activities in integrated farming activities (mixed farming: crops, fishponds, and livestock) is expected to provide added value in food security for farming families. The research objective was to determine the characteristics of Java Ethnic pekarangan to support food security in Karang Mumus Watershed East Kalimantan. The research was conducted from March to August 2013 at Javanese pekarangan in Karang Mumus Watershed East Kalimantan. Research using surveys, questionnaires, and interviews, as well as literature. The results showed that the average area of pekarangan owned by farmers is 2,160 m2. Pekarangan managed as agroforestry systems. The pekarangan is growing with particularly high diversity of plant species of perennial crops and ornamental plants. Pekarangan which has a kind of perennial crops such as coconut that is closely related to Javanese culture as much as 79.2%. Javanese pekarangan also has a 66.7% livestock animals (chickens, ducks, pigeons, and goats) and 20.8% had fish. The agrosilvopastura pekarangan has a total value of receipts and revenue be compared to the largest agrisilvikultur, agrosilvofishery, and agrosilvopasturafishery Rp. 91,775,000 per growing season and Rp. 77,538,690 per growing season.